Poverty reduction and development national strategies and a case study of ADB funded pilot project in Nayong County in Guizhou Province, People Republic of China. - Sapkota, Nogendra (Metro Manila, Philippines Asian Development Bank, 2017)
Poverty reduction is a challenging task. It requires sound national poverty reduction strategies and good local practices. Over the past 3 decades the People Republic of China (PRC) has implemented several poverty reduction programs and has lifted the majority of its population from poverty. This paper provides an overview of the PRC national poverty reduction strategies and highlights a case study of a pilot project in Nayong County of Guizhou Province that was funded by ADB. It shows how national poverty reduction strategies and local-level projects can contribute successfully to poverty reduction and development.
Keywords: Poverty -- China; social rights -- China; Electronic books